Proceedings of the International Conference on Management, Accounting, and Economy (ICMAE 2020) 2020
DOI: 10.2991/aebmr.k.200915.051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media Influencer Marketing on the Intention to Buy Online Through Attitude on Advertising and Brands

Abstract: This research aims to study the impact of influencers through social media which is focused on Influencer's Credibility, Influencer's Attractiveness, Fit-Influencer-Product Level and Meaning Transfer on the intention to buy online through Consumer Attitudes towards Advertising and Consumer Attitudes towards Brands. The method used for data analysis is to use Structural Equation Modeling (SEM). The questionnaire was collected from two hundred and sixty-five consumers who had bought fashion products online. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Many studies have stated that attitude towards the influencer can influence consumer purchasing decisions, as stated by (von Felbert et al, 2020), (Trivedi et al, 2020), and Chetioui ( 2019), but it is different from the research conducted by Windy and Renny (2020). In addition, there are several exceptions submitted by Venus and Muqaddam (2019), which state that attitude towards the influencer affects the brand, in the sense that if the brand is only displayed through social media stories, it will not affect the brand conveyed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies have stated that attitude towards the influencer can influence consumer purchasing decisions, as stated by (von Felbert et al, 2020), (Trivedi et al, 2020), and Chetioui ( 2019), but it is different from the research conducted by Windy and Renny (2020). In addition, there are several exceptions submitted by Venus and Muqaddam (2019), which state that attitude towards the influencer affects the brand, in the sense that if the brand is only displayed through social media stories, it will not affect the brand conveyed.…”
Section: Introductionmentioning
confidence: 95%
“…This study also uses attitude toward the advertisement as a mediating variable because the activities carried out by these fashion influencers are advertising by creating trends and fashions uploaded on social media that their followers follow. This is a novelty of this study because the research conducted by Chetioui (2019) does not mention the attitude toward the advertisement variable, while this is considered necessary to measure the skills possessed by influencers (von Felbert et al, 2020;Windy et al, 2020;and Hanna., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Freberg et al (2011) also concluded that influencers are a new sort of independent third-party endorsers who can affect consumers' attitudes through social media. However, according to Astuti et al (2020), it is crucial to choose appropriate influencers to attract consumers' buying interest in the product. Therefore, companies have to consider the components that make consumers interested in the product being advertised because messages through influencers on social media are more credible and trustworthy (Deraman et al, 2020).…”
Section: Influencersmentioning
confidence: 99%
“…Different forms of online advertising also influence purchasing decisions on online platforms (De Haan, Wiesel, & Pauwels, 2016). Direct product marketing influences online purchase intention through attitudes towards advertising and brands (Astuti & Risqiani, 2020). The advantage is that convenience and time saving are most important in online shopping (Hanus, 2016) Online consumers have easier access to information and a wide range of products and services at competitive prices (Suhaily & Soelasih, 2017).…”
Section: Theoretical Basis and Theory Development Product Attributesmentioning
confidence: 99%